Classification of anemia in hemodialysis patients in relation to vascular access and its correlation with hepcidin and ferritin - Al-Rubaie, Haithem A.; Hasan, Dhalal D.; Al-Rubaye, Raid A. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: Anemia is very common in patients with chronic kidney disease, and becoming almost universal in end stage renal disease, where dialysis or renal transplantation becoming the treatment of choice. High levels of hepcidin appear to accompany reduced renal function and serum ferritin may also be elevated.Objectives: To classify anemia in hemodialysis patients and to display the correlations between the types of anemia and inflammatory parameters like hepcidin and ferritin according to vascular access of hemodialysis.Patients and methods: This case-control study was conducted at Al-Hayat center for hemodialysis, and included 60 adult patients on hemodialysis. Also 20 healthy individuals were recruited as control group. Measurement of hemoglobin, erythrocyte sedimentation rate, transferrin saturation percentage, serum ferritin, C-reactive protein and hepcidin were done. Anemic patients were classified into; anemia of chronic disorder, iron deficiency anemia, combined, and others. Patients were also divided into two groups depending on their vascular access of hemodialysis.Results: Anemia of chronic diseases was the most frequent anemia (45%) among the patients followed by combined anemia of chronic diseases/iron deficiency anemia then iron deficiency and other causes. No significant difference was observed between types of anemia and inflammatory parameters according to patients’ vascular access of hemodialysis. There was no significant difference in the mean levels of hepcidin, ferritin, ESR and CRP of the patients according to the vascular access of hemodialysis, while hemoglobin level of patients with anemia of chronic in double lumen was significantly lower than those with arteriovenous fistula, P= 0.007.Conclusions: Anemia of chronic diseases was the most frequent in hemodialysis patients. There are higher levels of inflammatory parameters in hemodialysis patients than healthy controls.